2009
DOI: 10.1200/jco.2008.21.2738
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Conformal Radiation Therapy for Pediatric Patients With Low-Grade Glioma: Prospective Evaluation of Cognitive, Endocrine, and Hearing Deficits

Abstract: A B S T R A C T PurposeWe conducted a prospective trial to evaluate late effects in pediatric patients with low-grade glioma (LGG) treated with conformal radiation therapy (CRT). Patients and MethodsBetween August 1997 and August 2006, 78 pediatric patients with LGG (mean age, 9.7 years; standard deviation, Ϯ4.4 years) received 54 Gy of CRT with a 10-mm clinical target volume margin. Tumor locations were diencephalon (n ϭ 58), cerebral hemisphere (n ϭ 3), and cerebellum (n ϭ 17). Baseline and serial evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
254
4
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(273 citation statements)
references
References 29 publications
8
254
4
7
Order By: Relevance
“…Data regarding long-term toxicity of radiotherapy were reported in multiple studies. However, very few patients with BSLGT were included in these studies [26,29]. Edwards et al reported excellent short-term functional outcome following irradiation in five patients with focal brainstem astrocytomas [30].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding long-term toxicity of radiotherapy were reported in multiple studies. However, very few patients with BSLGT were included in these studies [26,29]. Edwards et al reported excellent short-term functional outcome following irradiation in five patients with focal brainstem astrocytomas [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported an increased risk for vascular events and secondary radiation-induced malignancies, 18,43,44 and long-term survival after radiation has not been addressed adequately. Our study raises major concerns regarding the association of radiotherapy with increased overall and tumor-related late deaths.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] However, in the context of a low-grade tumor, potential sequelae associated with radiotherapy are a major concern, especially in young children. 13,17,18 The comparison of previous studies is often inconclusive; newly recognized pathological entities such as pilomyxoid astrocytoma and pleomorphic xanthoastrocytoma were not described in older studies, 10,11,19,20 some studies incorporated patients diagnosed before the widespread use of magnetic resonance imaging, 5 and others used series from referral centers, where patient bias exists. 21,22 The National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database 5 and Childhood Cancer Survivor Study [23][24][25][26] have been valuable resources in the study of the long-term outcomes of pediatric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Neurokognitivne funkcije koje su osetljive na doze RT su brzina procesiranja, verbalno rezonovanje i pamćenje, vizuelna percepcija, jezik i akademsko postignuće. Levi temporalni režanj je podložan propadanju kada se taj deo zrači većim dozama zračenja kao i kada se zrači ceo mozak i supratentorijalni deo (45Gy) što je povezano sa lošijim intelektualnim funkcionisanjem [47] NEUROKOGNITIVNA PROCENA Američka Akademija za pedijatriju i Grupa za pedijatrijsku onkologiju (COG -Children Oncology Group) pored ostalih standarda, propisali su i standard vezan za obaveznu neuropsihološku procenu i praćenje dece i mladih koji se leče od tumora CNS-a. Neuropsihološka procena prema navedenim preporukama podrazumeva procenu inteligencije, brzinu procesiranja, akademsko postignuće, pamćenje, pažnju i koncentraciju, vizuo-motornu i vizuospacijalnu organizaciju, verbalnu fluentnost, egzekutivne funkcije i planiranje (2).…”
Section: Neurokognitivne Posledice Tumora Cns-a Kod Dece I Mladihunclassified